Evaluating the Joint Visit Program Using the CIPP Model in Food Tax Collection in Surakarta - Anisa Rahmawati (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
The joint visitation program by the Regional Revenue Agency (Bapenda) of Surakarta City and KPP Pratama Surakarta aims to improve the accuracy of local tax data on food and beverages in the wedangan business sector, where reliable information is crucial for fair tax assessment. This qualitative study evaluated the program’s implementation through direct observation, document review, and semi-structured interviews. The Context, Input, Process, and Product (CIPP) evaluation model, combined with a summative evaluation approach, was applied to assess overall effectiveness. The visitation documented customer numbers, menu prices, and estimated daily turnover as the basis for tax calculation. Findings reveal several challenges, including limited observation periods, taxpayer resistance to recorded data, the absence of stakeholders during clarification, and negotiated tax liabilities that were lower than the actual observation results. Extending observation periods and adopting digital technologies for real-time monitoring may enhance accuracy and transparency. Persuasive communication strategies can help reduce taxpayer resistance, while strict enforcement of observation results is essential to maintain data integrity. This study contributes to the understanding of local tax policy evaluation by highlighting practical strategies to strengthen tax administration in the wedangan sector.